2016
DOI: 10.18632/oncotarget.10412
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide inhibits cell growth and GRP78 protein expression but induces cell apoptosis in original and radioresistant NPC cells

Abstract: The radioresistance is the key factor to hamper curative effect and survival of nasopharyngeal carcinoma (NPC) patients. Nature triptolide (TPL) has been found to circumvent drug-resistant effect of cancer, but its effect on NPC radioresistance has been rarely studied. In the present study, the 10 Gy-resistant CNE2 subclones (CNE2-SR) were used as a NPC radioresistant model. The IC50 of TPL in CNE2 and CNE2-SR cells was measured by MTT assay, cell cycle was analyzed by flow cytometry, and protein expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In addition, the changes of GRP78 expression have also been revealed to play key functions in the development and progression of malignant tumors ( 9 ). GRP78 has been revealed to be a therapeutic target of NPC ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the changes of GRP78 expression have also been revealed to play key functions in the development and progression of malignant tumors ( 9 ). GRP78 has been revealed to be a therapeutic target of NPC ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that malignant cells expressed higher levels of HSP70 than normal cells, and high expression of HSP70 induced resistance to radiotherapy through different mechanisms [ 175 , 176 ]. Thus, HSP70 inhibitors, such as triptolide which enhanced cellular radiosensitivity by inhibiting HSPA5 to trigger apoptosis and induce G 2 /M cell cycle arrest in nasopharyngeal carcinoma, can be used as radiosensitizers in radiation therapy [ 177 ]. Of note, the level of HSP70 was also upregulated in cancer cells treated with heat or light, leading to the low therapeutic efficiency in tumors [ 178 , 179 ].…”
Section: Targeting Hsp70 In Cancer Therapymentioning
confidence: 99%
“…Lung cancer Induction of HSP70 expression and AKT phosphorylation by Redd1 to acquire resistance to radiotherapy Jin et al (2019) Nasopharyngeal carcinoma TPL (HSP70 inhibitor) enhances cellular radiosensitivity by inhibiting GRP78 to trigger apoptosis and induce G2/M phase arrest Li et al (2016) Endometrial cancer Silencing of HSP70 expression enhances radiotherapy efficacy Du et al (2009) folding, however, this is likely not its direct role in the cell death pathway. Beere et al (2000) first suggested in 2000 that HSP70 could inhibit apoptosis by directly binding specifically to Apaf-1 to block the assembly of the apoptotic complex, but it could not block Fas-induced apoptosis.…”
Section: Cancer Type Findings Referencesmentioning
confidence: 99%
“…In addition, inhibition of HSP70 expression significantly inhibits tumor cell growth and induces cell cycle arrest (Lin The DNA damage caused by radiotherapy leads to the activation of cell cycle regulatory mechanisms by the relevant genes, causing cell cycle arrest at two checkpoints, the G1/S phase and the G2/M phase, and the blockage of cell cycle checkpoints is an important determinant of the radiosensitivity of tumor cells (Figure 4). HSP70 inhibitors can radiosensitize tumors by inhibiting HSP70-induced cell cycle checkpoint arrest, as in nasopharyngeal carcinoma TPL can trigger apoptosis and induce G2/M phase arrest by inhibiting GRP78, thus TPL can be used as a new radiosensitizer for the treatment of nasopharyngeal carcinoma (Li et al, 2016).…”
Section: Cell Cycle Blockadementioning
confidence: 99%